INTERVENSI KEMANUSIAAN SEBAGAI CARA PENYELESAIAN KONFLIK DAN PELANGGARAN HAK ASASI MANUSIA DI MYANMAR - Yogi Yudha Ksatria (2022)
Myanmar has been in a conflict since the Military Junta seized power through a coup on February 1, 2021. The conflict has killed many civilians. Humanitarian intervention is a way that can be used to resolve conflicts and human rights violations. Humanitarian intervention is an intervention carried out by one or several countries against other countries to prevent or end suffering and human rights violations. This article aims to examine the role of the United Nations (UN) in implementing humanitarian intervention, then how to use humanitarian intervention as a way to resolve conflicts and human rights violations in Myanmar from the perspective of international law. The research method used is normative legal research with a statutory approach and conceptual approach. The results of this study show that the UN has a very important role in the implementation of humanitarian intervention. The United Nations Charter Chapter VII states that military intervention can be carried out to maintain international peace and security. The use of humanitarian intervention as a means of resolving conflicts and human rights violations in Myanmar can be carried out if four elements of justification have been met, namely the situation in Myanmar, the existence of a basis and concept or theory of international law that can support it, the mistakes of the Myanmar government, and the approval or authorization from the UN Security Council. Currently, there is one element that has not been fulfilled, namely approval or authorization from the UN Security Council.